Atom‐by‐Atom Fabrication of Monolayer Molybdenum Membranes. Issue 23 (30th April 2018) - Zhao, Xiaoxu; Dan, Jiadong; Chen, Jianyi; Ding, Zijing; Zhou, Wu; Loh, Kian Ping; Pennycook, Stephen J.
Abstract: Fabrication of materials in the monolayer regime to acquire fascinating physical properties has attracted enormous interest during the past decade, and remarkable success has been achieved for layered materials adopting weak interlayer van der Waals forces. However, the fabrication of monolayer metal membranes possessing strong intralayer bonding remains elusive. Here, suspended monolayer Mo membranes are fabricated from monolayer MoSe2 films via selective electron beam (e‐beam) ionization of Se atoms by scanning transmission electron microscopy (STEM). The nucleation and subsequent growth of the Mo membranes are triggered by the formation and aggregation of Se vacancies as seen by atomic resolution sequential STEM imaging. Various novel structural defects and intriguing self‐healing characteristics are unveiled during the growth. In addition, the monolayer Mo membrane is highly robust under the e‐beam irradiation. It is likely that other metal membranes can be fabricated in a similar manner, and these pure metal‐based 2D materials add to the diversity of 2D materials and introduce profound novel physical properties. Abstract : The fabrication of a monolayer Mo membrane by selective sputtering of Se atoms from a freestanding monolayer MoSe2 film is demonstrated. The nucleation and subsequent growth of the Mo membranes are triggered by the formation and aggregation of Se vacancies. Various novel structural defects and intriguing self‐healing characteristics are unveiled during the growth and the monolayer Mo membrane is highly robust under electron‐beam irradiation.